Assessing access to information and communication technologies in the educational sector in east Algeria: Constantine, Annaba, and Setif as study models - Aloui, Hind (Journal of Human Sciences, 2022)
Educational technology is an application of advanced technologies such as computers, and satellites… In a broader sense, information technologies can be used to plan, execute, evaluate, and improve the different facets of the education process. Through this study, we aim to elucidate how information technologies are integrated in the education sector, and how to evaluate the access to these technologies in the education sector in the studied states, namely Constantine, Annaba, and Setif.